1995
DOI: 10.1056/nejm199510193331603
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of Cellular Immunity against Cytomegalovirus in Recipients of Allogeneic Bone Marrow by Transfer of T-Cell Clones from the Donor

Abstract: The transfer of CMV-specific clones of CD8+ T cells derived from the bone marrow donor is a safe and effective way to reconstitute cellular immunity against CMV after allogeneic marrow transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
1,167
0
9

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,693 publications
(1,203 citation statements)
references
References 34 publications
27
1,167
0
9
Order By: Relevance
“…Data from both mouse and human allogeneic studies have shown that donor T cells exhibit decreased allo-reactivity and GVHD potential following ex vivo activation and expansion [2][3][4][5][6]. This loss of allo-reactivity is extremely undesirable because both the conversion to full donor chimerism and the anti-leukemia effect after allogeneic HSCT are mediated, at least in part, by alloreactive donor T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from both mouse and human allogeneic studies have shown that donor T cells exhibit decreased allo-reactivity and GVHD potential following ex vivo activation and expansion [2][3][4][5][6]. This loss of allo-reactivity is extremely undesirable because both the conversion to full donor chimerism and the anti-leukemia effect after allogeneic HSCT are mediated, at least in part, by alloreactive donor T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the therapeutic strategies that are being developed to control GVHD while maintaining the beneficial graft-versus-leukemia and/or graft-versus-infection effects provided by donor lymphocyte infusion after allogeneic HSCT require ex vivo T cell stimulation and expansion. Unfortunately, multiple preclinical and clinical studies have demonstrated that these ex vivo expanded T cells exhibit decreased survival and function in vivo, including reduced alloreactivity and GVHD potential [2][3][4][5][6]. Recently, others and we described an ex vivo method for expansion of human T (huT) cells, using anti-CD3 and anti-CD28 monoclonal antibodies that are covalently attached to superparamagnetic microbeads (CD3/CD28 beads) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Antivirals also favor late-onset CMV disease [4], and the occurrence of resistant CMV strains [5]. In search of therapeutic alternatives, the reconstitution of protective T cell immunity by adoptive transfer of CMV-specific T cells has been successfully performed [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, clinical studies on CMV indicated that the acquisition of both CD8 + and CD4 + antigen-specific T cells was necessary for long-term maintenance of specific T cell immunity and therapeutic efficacy [5,7,8]. CD4 + T cells have an important role in the establishment of a functional CD8 + T cell memory [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that there is generally a similar requirement to help the CTL response [4,5]. This applies also to adoptive transfer of CTL to attack viruses such as CMV, where the transferred CTL only survive and function efficiently with co-transferred Th cells [6].…”
Section: Importance Of T-cell Helpmentioning
confidence: 99%